An Auto-luminescent Fluorescent BCG Whole Blood Assay to Enable Evaluation of Paediatric Mycobacterial Responses Using Minimal Blood Volumes - Basu Roy, Robindra; Sambou, Basil; Uhía, Iria; Roetynck, Sophie; Robertson, Brian D.; Kampmann, Beate (Frontiers in Pediatrics, 2019)
Introduction: Understanding protective human immunity against mycobacteria is critical to developing and evaluating new vaccines against tuberculosis. Children are the most susceptible population to infection, disease, and death from tuberculosis, but also have the strongest evidence of BCG-inducible protection. Limited amounts of blood can be obtained for research purposes in paediatrics and therefore there is a need for high-yield, low-volume, human immunology assays. Methods: We transformed BCG Danish with plasmids encoding luciferase full operon derived from Photorhabdus luminescens together with Green Fluorescent Protein and antibiotic selection markers. We characterised the luminescent and fluorescent properties of this recombinant BCG strain (BCG-GFP-LuxFO) using a luminometer and flow cytometry and developed a paediatric whole blood in vitro infection model. Results: Luminescence of BCG-GFP-LuxFO correlated with optical density (Spearman Rank Correlation coefficient r=0.985, p<0.0001) and colony forming units (CFUs) in liquid culture medium (r=0.971, p<0.0001). Fluorescence of BCG-GFP-LuxFO in paediatric whole blood was confirmed by flow cytometry in granulocytes and monocytes one hour following infection. Luminescence of BCG-GFP-LuxFO in whole blood corresponded with CFUs (r= 0.7123, p<0.0001). Conclusion: The BCG-GFP-LuxFO assay requires 225 microlitres whole blood per sample, from which serial luminescence measurements can be obtained, together with biochemical analysis of supernatants and cellular assay applications using its fluorescent properties. This offers the opportunity to study human-mycobacterial interactions using multiple experimental modalities with only minimal blood volumes. It is therefore a valuable method for investigating paediatric immunity to tuberculosis.